Breaking Barriers: The Evolving Landscape of Gender Equality and Anti-Discrimination in Sustainable Development - Ivaniuk, Ruslan; Karvatska, Svitlana; Toronchuk, Ivan; Ilika, Maryna; Gnatuyk, Tetyana (Bucharest University of Economic Studies, 2024)
This article explores the crucial role of gender equality and anti-discrimination efforts in achieving the Sustainable Development Goals (SDGs), focusing particularly on Goal 5 of the UN's 2030 Agenda. Employing a mixed-methods approach, the study integrates quantitative and qualitative analyses, reviewing strategic documents, statistical data, and case studies. It highlights the significant impact of gender-based violence, economic disparities, and social inequalities on sustainable development. The paper examines key international frameworks, such as the Istanbul Convention and the EU's gender policies, and their implications for Ukraine. It discusses the progress and challenges Ukraine faces in promoting gender equality amidst the ongoing war and its socio-economic impacts. The article concludes with recommendations for enhancing policy implementation, fostering international cooperation, and addressing the socio-economic impacts on gender equality. This comprehensive analysis aims to contribute to the global discourse on achieving gender equality as a cornerstone of sustainable development.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE